Realización del documental “A patria profunda” como piloto de una serie documental sobre la búsqueda personal de la patria y el orgullo - Durand de la Puente, Andrea (2022)
A patria profunda is a documentary series that explores the personal search for a connection with and pride of one’s homeland. The director seeks to understand her feeling of having no homeland through the understanding of people who do feel a deep connection with theirs. With that in mind, her starting point consists of three basic questions (what is “homeland? Where is the feeling of belonging to a certain homeland born? And finally, do we need a homeland?) designed to help her understand her subjects’ diverse perspectives on the topic. In this project, the second of four episodes is presented as a pilot. Its subject is Yvonne, a Dutch woman who was a backpacker for eight years during her youth and who has now been living in Peru for thirty three years. The episode has a duration of 16 minutes, is divided into three parts, and uses resources such as narration, motion graphics and archive material to portray not only Yvonne’s experiences, but also the director’s personal views and feelings about what is being told. This paper also presents the artistic and technical proposal of the documentary series as a whole, which, as a starting point, is made up of four episodes.